How Adolescents View Advertising: The Effects of Beliefs and Personal Values - Ernest Cyril, de Run; Hiram, Ting; Siew, Ling Liew (2014)
The purpose of this study is to investigate how adolescents view advertising. Specifically, the study utilizes the seven-belief factors model and the List of Values (LOVs) to look into the effects of beliefs about advertising and personal values on attitude towards advertising. Given the fact that little is known about adolescents’ views on the subject matter, and how the two antecedent variables affect their attitude in emerging markets, the Theory of Reasoned Action (TRA) was adapted to determine the attitude of Neoteric-inheritors (age ranged from 15 to 21 years old in the year of 2013) towards advertising. Selfadministered questionnaires were distributed in Sarawak, and 384 usable copies were subsequently collected and keyed in for analysis. The findings show that product information, social role/image, being good for the economy, not being materialistic and truthfulness have positive effect on attitude towards advertising. However, only internal value is found to be significant predictor of attitude towards advertising, albeit weak. The study thus provides insights into beliefs and attitude of adolescents towards advertising, and how the shaping of personal values may affect such attitude. Managerial implications of study are provided.